Contribuciones de Max Neef et al. a la teoría de las necesidades humanas - Boltvinik, Julio (El Colegio de México, 2024)
This study aims to critically evaluate the contributions of Max-Neef et al. to theories related to human needs. First, the fifteen postulates proposed by the authors are described, highlighting key contributions such as the definitions of needs, satisfiers, and goods, as well as their rates of change. Additionally, their matrix of needs and satisfiers is characterized as both attractive and thought-provoking, though insufficiently developed. In particular, the distinction between satisfiers and goods proves functional only when the satisfier is a human activity. Furthermore, it is noted that when goods become ends in themselves, the supposed satisfaction of needs hinders the ability to fully experience them, leading to an alienated society. The authors’ typology of satisfiers is also outlined, and a comparison is made between their framework of needs and eight other theoretical models.